Commitment of the Head of the Ministry of Religious Affairs in Increasing the Motivation for Achievement of Teachers Raudhatul Athfal within the Ministry of Religious Affairs of Sarolangun Regency - Apriadi, Apriadi; Maisah, Maisah; Kusnadi, Edi (Green Publisher, 2023)
Commitment Head of the Ministry of Religious Affairs in increasing the motivation of outstanding teacher Raudhatul Athfal within the Ministry of Religious Affairs of Sarolangun Regency. Based on the grand tour found still lacking. The research method uses a qualitative descriptive approach. Data collection is carried out by observation, interview and documentation techniques. Determination of research subjects using the snawboll sampling technique. Data analysis techniques are carried out by data reduction, data presentation and conclusion drawing and verification of the reliability of research results obtained by techniques of extension of participation, accuracy of observation, triangulation andata. The results showed that. The commitment of the Head of the Ministry of Religious Affairs in increasing the motivation of outstanding teachers Raudhatul Atfhal within the Ministry of Religious Affairs of Sarolangun Regency can be in the form of spective, normative and sustainable commitments. The factors causing the lack of commitment of the Head of the Ministry of Religious Affairs in increasing the motivation for the achievement of Raudhatul Athfal teachers are First, the Internal Factors that exist in the Head of the Ministry of Religion itself lack the enthusiasm to motivate teachers Raudhatul Athfal.Second External Factors from outside the Head of the Ministry of Religion such as lack of cooperation with the community, Regional Government, Provincial Ministry of Religion and Central Ministry. The strategy of the Head of the Ministry of Religion for improving the Motivation for Teacher Achievement Raudhatul Athfal can be in the form of providing coaching, training and including seminars and improving higher education